Profile and Career Decisions of First Year Medical Students Studying at a College Located in western India - Shobha Misra; Nilesh Fichadiya (Indian Association of Preventive and Social Medicine, 2021)
Introduction:The attitude of the students and the reasons for choosing a career, medicine in particular are of importance as input for educators to create a medical graduate.Objectives:To get an account of medical students' reasons for choosing medicine and to document qualities of a good doctor as perceived by them. Method: Cross-sectional study was conducted through self-administered & semi- structuredquestionnaire in August 2019, at a government run Medical College of India to a batch of 200 students. Results: Majority of students were involved in some kind of sports. Honesty, good communication skills, desire to serve humanity, patience were qualities of good doctor quoted by majority of them while compassion, empathy, clinical acumen was mentioned by less than half of them. Majority of them listed self-interest or passion as the predominant reason to choose medicine as a career.A fifth of the students mentioned influence of Family or Parents as reasons to join the course. Conclusion: Compassion, empathy, Clinical acumen as qualities of a good doctor was mentioned by less than half of them. During the one month foundation program and professionalism modules the areas identified can be stressed upon.